A Survey of Acupuncture-Providing Registered Massage Therapists in Ontario, Canada: Motivation, Training, and Practice Characteristics - Ijaz, MSc, PhD, Nadine; Welsh, PhD, Sandy; Boon, BScPhm, PhD, Heather (International Journal of Therapeutic Massage & Bodywork, 2020)
Background: An increasing number of licensed massage therapists in several countries are providing acupuncture to their clients, but little is known about this practice. Purpose: To characterize the motivations, training backgrounds, practice patterns, and clinical experiences of licensed massage therapists who perform acupuncture. Research Design: The study used a cross-sectional, online survey design involving acupuncture-providing registered massage therapists (RMTs) in the province of Ontario, Canada, where acupuncture is explicitly permitted within the massage therapy profession’s scope. Analysis involved descriptive statistics and thematic content analysis of qualitative findings. Results: The survey response rate was 33.7% (n=212), representing 25.5% of all Ontario RMTs rostered to practice acupuncture. Participant demographics mirrored the RMT profession as a whole, except that providers were, on average, several years older than other RMTs. Most respondents (72.7%) had completed over 200 hours of training in acupuncture; most training included clean needle technique (96.8%), clinical supervision (93.5%), traditional Chinese medicine content (83.4%), and a final examination (96.8%). Respondents typically used acupuncture in about one-third of their sessions (mean 32.3%, SD 5.0) with an average of 10.5 weekly clients (SD 14.3). Acupuncture-providing RMTs had been initially motivated by acupuncture’s potential effectiveness for musculoskeletal conditions (97.2%), a wish to attract more clients (61.3%), and physical fatigue from delivering manual therapies (48.3%). Most reported being more likely to achieve excellent clinical results (84.9%), experience greater professional satisfaction (79.9%), and attract or retain clients (64.8%) since using acupuncture. A minority also reported earning a higher income (34.6%) and experiencing more adverse events in practice (21.5%). Qualitative responses added explanatory nuance to numeric results. Conclusions: This study of the use of acupuncture by Ontario’s licensed massage therapists represents a first scholarly account of an emerging global trend that holds promise in enhancing clinical care, professional stability, and provider longevity. Additional research is needed to investigate the practice’s use in other jurisdictions, and to establish international standards for safe and effective practice.